Pengaruh Net Profit Margin, Operating Profit Margin, Debt to Asset Ratio, dan Total Asset Turn Over terhadap Harga Saham Perusahaan Pertambangan Sub Sektor Batu Bara yang Terdaftar di BEI tahun 2019 – 2023 - Aini, Nurul; Tristanto, Triyono Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This research to evaluate impact of Net Profit Margin (NPM), Operating Profit Margin (OPM), Debt to Total Asset Ratio (DAR), and Total Asset Turnover (TATO) on the stock value of coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The sample comprises six firms selected through a non-random procedure using predetermined criteria in accordance with the purposive sampling method. Data analysis was conducted using SPSS. The findings indicate that NPM, DAR, and TATO individually exert a significant effect on stock prices, whereas OPM does not display a statistically significant influence. Collectively, all independent variables demonstrate a significant impact on stock prices, as reflected by an F-statistic of 9.256, which surpasses the F-table value of 2.76. The coefficient of determination (R²) of 0.597 shows that 59.7% of the variation in stock prices is accounted for by the combined variables NPM, OPM, DAR, and TATO, while the remaining 40.3% is attributed to external factors.